EFFECT OF INCLUSION OF CITRUS PULP IN XARAES GRASS SILAGE - Yasuoka, Junior Issamu [UNESP]; Lima Meirelles, Paulo Roberto de [UNESP]; Berchiol da Silva, Marina Gabriela [UNESP]; Granuzzo, Jonas Teixeira [UNESP]; Silva, Marcia Pereira da [UNESP] (Inst Zootecnia, 2015)
The objective of this study was to evaluate the effect of inclusion of different levels of pelleted citrus pulp (PCP) on the quality of xaraes grass silage. Xaraes grass was ensiled at 54 days of growth with 0, 10, 20 and 30% PCP and divided into 20 experimental silos (five repetitions/treatment). A completely randomized design was adopted. The silos were opened after 67 days for the determination of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), pH, and titratable acidity of the silages. The inclusion of PCP did not influence DM content, but reduced CP content. NDF and ADF content decreased with the addition of citrus pulp. Regarding pH, a significant difference was only observed for the inclusion of 30% PCP. Titratable acidity in the silage was lower in the absence of PCP (0%) compared to the treatment with 30% (P<0.05). The inclusion of 30% PCP in xaraes grass silage is indicated since it improves the quality of the fibrous fraction, while maintaining acceptable pH values.
Keywords: additive; chemical composition; subproduct